EFFECTIVENESS OF PAPAYA LEAF EXTRACT (Carica Papaya L.) IN THE TREATMENT OF KOI FISH (Cyprinus Rubrofuscus) SEEDS INFECTED WITH AEROMONAS HYDROPHILA BACTERIA - Silaen, Yuli Marlina; Istyadji, Maya; Yulinda, Ratna (Transpublika Publisher, 2023)
One of the most popular freshwater fish species to farm, both domestically and internationally, is the koi fish (Cyprinus Rubrofuscus). However, koi fish farming is often attacked by bacterial diseases caused by the Aeromonas hyrophila bacterium, so it becomes a concern because this bacterium can cause death in koi fish. Papaya leaves were chosen as an alternative medicine in the treatment of koi fish infected with bacteria, considering that papaya leaves contain many compounds that are antibacterial and have no side effects when used. As for this study, the papaya leaves used were young papaya leaves which were extracted using the maceration method. This study was aimed to determine the effectiveness in treating koi fish infected with bacteria and what concentration of papaya leaf extract is effective as an antibacterial to treat koi fish seeds that are attacked by Aeromonas hydrophila bacteria. Papaya leaf extract was administered at different concentrations, namely 0 ml (control), 5 ml, 10 ml, 15 ml within 30 days before and after the koi fish seeds were attacked by Aeromonas hydrophila. The result revealed that papaya leaf extract has effectiveness as an antibacterial which can slow down the growth of Aeromonas hydrophila bacteria at a concentration of 15 ml with a survival rate of 95%. Therefore, the dose of papaya leaf extract is directly proportional to its effectiveness as an antibacterial. In other words, the greater the dose of papaya leaf extract, the more effective it will be in treating koi fish seeds that are infected with bacteria.